2022
DOI: 10.2147/cmar.s349884
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Bioinformatics Analysis and Validation of the Prognostic Value of RBM10 Expression in Hepatocellular Carcinoma

Abstract: Background RBM10ʹ s function in hepatocellular carcinoma (HCC) has rarely been addressed. We intend to explore the prognostic significance and therapeutic meaning of RBM10 in HCC in this study. Methods Multiple common databases were integrated to analyze the expression status and prognostic meaning of RBM10 in HCC. The relationship between RBM10 mRNA level and clinical featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
(27 reference statements)
2
4
0
Order By: Relevance
“…In this study, we found that the RBM10 expression was negatively correlated with B cells, CD8+ T cells, neutrophils, macrophages, and DC cell infiltration levels in most tumor types, indicating that RBM10 was likely to affect tumor development and prognosis by impacting the tumor microenvironment. It is worth noting that in HCC, RBM10 was significantly positively correlated with a variety of immune cells, which was consistent with the results of Pang et al [8]. In addition, we further found that the RBM10 expression was closely related to tumor-associated macrophages (TAMs) in a variety of cancers through xCell.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, we found that the RBM10 expression was negatively correlated with B cells, CD8+ T cells, neutrophils, macrophages, and DC cell infiltration levels in most tumor types, indicating that RBM10 was likely to affect tumor development and prognosis by impacting the tumor microenvironment. It is worth noting that in HCC, RBM10 was significantly positively correlated with a variety of immune cells, which was consistent with the results of Pang et al [8]. In addition, we further found that the RBM10 expression was closely related to tumor-associated macrophages (TAMs) in a variety of cancers through xCell.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, the correlation of the RBM10 expression with tumor stages was reported to be negative in pancreatic cancer [25]. The correlation of high expression of RBM10 in HCC with more advanced tumor stages was significantly positive [8]. Additionally, our prognostic analysis indicated that in certain malignancies, the high RBM10 expression was a risk factor and was considerably linked to the poorer OS, PFS, and RFS.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations